Developments in synthesis, characterization, and application of large, high-quality CVD single crystal diamond - Liang, Q.; Meng, Y.-F.; Yan, C.-S.; Krasnicki, S.; Lai, J.; Hemawan, K.; Shu, H.; Popov, D.; Yu, T.; Yang, W.; Mao, H.K.; Hemley, R.J. (Сверхтвердые материалы, 2013)
Single crystal diamond synthesis by microwave plasma chemical vapor deposition at rapid growth rate has considerably advanced in the past few years. Developments have been made in growth, optical quality, and mechanical properties. Of the various types of single crystal diamond that can be produced using these techniques, high quality single crystal CVD diamond can be routinely produced, and this material is playing an increasing role in research on materials under extreme conditions. This article highlights recent developments in single crystal CVD diamond synthesis and characterization, as well as various applications in high-pressure materials research. За останні кілька роки синтез монокристалів алмазу мікрохвильовим плазмовим хімічним осадженням з газової фази з високою швидкістю значно просунувся. Прогрес було досягнуто у рості, оптичних і механічних властивостях. З різних типів монокристалічного алмазу, що можна отримати з використанням цього методу, регулярно виробляють високоякісні монокристалічні CVD-алмази, і цей матеріал відіграє все більш важливу роль при дослідженні матеріалів в екстремальних умовах. У даній роботі висвітлено останні досягнення в синтезі монокристалічного CVD-алмазу і дослідженні його характеристик, а також його різне застосування у дослідженні матеріалів при високому тиску. За последние несколько лет синтез монокристаллов алмаза микроволновым плазменным химическим осаждением из газовой фазы с высокой скоростью значительно продвинулся. Прогресс был достигнут в росте, оптических и механических свойствах. Из различных типов монокристаллического алмаза, которые могут быть получены с использованием этого метода, регулярно производят высококачественные монокристаллы CVD-алмаза, и этот материал играет все более важную роль в исследовании материалов в экстремальных условиях. В этой работе осветлены последние разработки в синтезе монокристаллов CVD-алмаза и исследовании его характеристи